Treatment and outcomes of older versus younger women with HER2-positive metastatic breast cancer in the real-world national ESME database. (December 2021) - Annonay, Mylène; Gauquelin, Lisa; Geiss, Romain; Ung, Mony; Cristol-Dalstein, Laurence; Mouret-Reynier, Marie-Ange; Goncalves, Anthony; Abadie-Lacourtoisie, Sophie; Francois, Eric; Perrin, Christophe; Le Fel, Johan; Lorgis, Véronique; et al.
Abstract: Background: Treatment and outcomes of patients with HER2-positive (HER2+) metastatic breast cancer (MBC) have dramatically improved over the past 20 years. This work evaluated treatment patterns and outcomes according to age. Methods: Women who initiated a treatment for HER2+ MBC between 2008 and 2016 in one of the 18 French comprehensive centers part of the ESME program were included. Objectives were the description of first-line treatment patterns, overall survival (OS), first-line progression-free survival (PFS), and prognostic factors among patients aged 70 years or more (70+), or less than 70 (<70). Results: Of 4045 women diagnosed with an HER2+ MBC, 814 (20%) were 70+. Standard first-line treatment (chemotherapy combined with an anti-HER2 therapy) was prescribed in 65% of 70+ versus 89% of <70 patients (p < 0.01). Median OS was 49.2 (95% CI, 47.1–52.4), 35.3 (95% CI, 31.5–37.0) and 54.2 months (95% CI, 50.8–55.7) in the whole population, in patients 70+ and <70, respectively. Corresponding median PFS1 were 12.8 (95% CI, 12.3–13.3), 11.1 (95% CI, 10.0–12.3) and 13.2 months (95% CI, 12.7–13.9), respectively. In 70+ women, initiation of non-standard first-line treatment had an independent detrimental time-varying effect on both OS and PFS (HR on OS at 1 year: chemotherapy without anti-HER2 2.79 [95% CI: 2.05–3.79]; endocrine therapy and/or anti-HER2 1.96 [95% CI: 1.43–2.69]). Conclusions: In this large retrospective real-life database, older women with HER2+ MBC received standard first-line treatment less frequently than younger ones. This was independently associated with a worse outcome, but confounding factors and usual selection biases cannot be ruled out. Highlights: Only 65% of women aged 70+ with HER2+ MBC receive a standard first-line treatment. Median PFS1 of women 70+ with HER2+ MBC is 11.1 months (95% CI, 10.0–12.3) vs 13.2 (95% CI, 12.7–13.9) for younger ones. Non-standard first-line treatment has a detrimental time-varying effect on both OS and PFS.